Combined oxidative phosphorylation deficiency type 7 caused by C12orf65 gene mutations: a case report and literature review - Chen, Xiao-Yi; Zhu, Yong-Jie; Deng, Jie; Ma, Yan-Li; Suo, Jun-Fang; Wang, Yuan; Ma, Yuan-Ning (Zhongguo dang dai er ke za zhi, 2025)
To investigate the clinical features and gene mutation characteristics of combined oxidative phosphorylation deficiency type 7 (COXPD7) caused by mutations in the gene, and to enhance the awareness of this disease. A child diagnosed with COXPD7 in the Department of Neurology, Children's Hospital Affiliated to Zhengzhou University in 2021 was included, along with 10 patients reported in the literature. All subjects were analyzed for their genotypes and clinical phenotypes. A total of 11 patients with COXPD7 were included, comprising 1 reported in this study and 10 from the literature. Among the 11 patients, 9 had homozygous mutations in the gene, while 2 had compound heterozygous mutations, which were identified as frameshift or nonsense mutations. The age of onset ranged from 1 day to 2 years, and clinical manifestations included optic nerve atrophy and delays in intellectual and motor development. Eight patients exhibited external ophthalmoplegia, and five patients displayed spastic paralysis. Cranial magnet